Biogas from goat waste as a green energy source - Yarra Sutadiwiria; Mixsindo Korra Herdyanti; Mira Meirawaty; Himmes Fitra Yuda; Rendy Rendy; Riezky Kokky Mahendra; Gentala Ardikasa; Irina Letlora (Universitas Muhammadiyah Magelang, 2023)
Energy is one of the essential needs in the household sector. Sukasari Village in Rumpin District is one of the areas in Bogor, West Java, where some residents still use kerosene or firewood for their daily household needs. Burning kerosene or firewood will produce carbon emissions and can damage the environment. There needs to be an alternative source of clean energy that is both environmentally friendly and economical. Many goat farming operations in the Rumpin area generate waste, which has the potential to be converted into biogas and used as a source of clean energy. Based on the survey, the goats' waste is only processed into fertilizer. A solution for providing clean energy sources while utilizing goat waste is to create useful products for everyday live through training and socialization in the construction of biogas digester. Based on the activities, residents can understand the solution to providing clean energy sources through using goat manure waste and are interested in using biogas from goat manure waste for their daily household needs.